AN EVALUATION OF EDUCATIONAL SUPERVISION IN IMPROVING TEACHING QUALITY IN AKURE SOUTH LGA, ONDO STATE, NIGERIA - BUKOLA-OJUMU, Ebunoluwa Olajumoke; FADARE, Abigail Oluyemisi; OGBAINI, Clement Aliu (Jurnal Saintifik (Multi Science Journal), 2024)
This study examined an evaluation of educational supervision in improving teaching quality in Akure South LGA, Ondo State, Nigeria. Descriptive survey research design was employed in which a total sample of 120 Principals, Vice – principals, HOD’s, Subject Heads were randomly selected from a population of 2,224 teachers in Akure South Local Government Area of Ondo State, Nigeria. One research question and two hypotheses guided the conduct of the study. Findings revealed that both teachers and principals unanimously agreed with all the item of the ESTQQ (Educational Supervision Teaching Quality Questionnaire) that is, teachers’ qualification, experience, mastery of subject and classroom management and how it affects teaching quality in junior public secondary schools in Akure South LGA, Ondo State, Nigeria. Based on the findings, it was discovered that there is a wide array of challenges that educational supervision encounters in its mission to elevate teaching quality. Among these challenges are, the lack of adequate training programs for teachers, insufficient channels for effective communication between supervisors and the teacher, and a pervasive organizational climate that often stifles open dialogue and feedback. It was recommended that supportive environment promoting open communication among teachers and fostering trust and collaboration among staff is more effective and responsive toward educational supervision process.